2019
DOI: 10.1042/bsr20182297
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of oxymatrine against DSS-induced acute intestinal inflammation in mice via blocking the RhoA/ROCK signaling pathway

Abstract: Oxymatrine (OMT) is an important quinoxaline alkaloid that has a wide range of pharmacological effects and has been shown to alleviate ulcerative colitis due to its profound anti-inflammatory effects. The RhoA/ROCK (Rho kinase) signaling pathway has been shown to be related to the pathogenesis of several autoimmune diseases; however, the specific mechanisms of RhoA/ROCK signaling in inflammatory bowel disease (IBD) remain elusive. Therefore, we sought to determine whether OMT could ameliorate acute intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…In the current work, administration of oxymatrine in diabetic rats in group IIIb (diabetic-oxymatrine group) greatly preserved the cerebellar cortex structure and protected against the changes induced by DM. Oxymatrine was proved to have antioxidant properties evidenced by enhanced production of antioxidant enzymes such as catalase, GP-x and SOD (Wang et al, 2019). This was in agreement with the signi cant increment in the levels of GP-x and SOD that were detected in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the current work, administration of oxymatrine in diabetic rats in group IIIb (diabetic-oxymatrine group) greatly preserved the cerebellar cortex structure and protected against the changes induced by DM. Oxymatrine was proved to have antioxidant properties evidenced by enhanced production of antioxidant enzymes such as catalase, GP-x and SOD (Wang et al, 2019). This was in agreement with the signi cant increment in the levels of GP-x and SOD that were detected in our study.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that some studies had shown that Y-27632 only inhibits its activity, usually has no effect on its expression. 51,52 However, other studies have shown that Y-27632 inhibits ROCK1 through inhibiting its expression. 26,53 The different effects of Y-27632 on ROCK1 may be related to cell types.…”
Section: Discussionmentioning
confidence: 99%
“…High NO level may promote the inflammation and cause tissue damage. There was a significant increase in the NO level after colitis induction [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%